Precursors and Outcomes of Perceived Value in Achieving Student Loyalty in Open Distance Electronic Learning Institutions - Mbango, Phineas (International Journal of African Higher Education, 2022)
The Covid-19 pandemic resulted in contact universities entering the distance learning market, creating new competition for Open Distance Electronic Learning (ODeL) institutions. To achieve a sustainable competitive advantage, these institutions need to formulate sound strategies to attract and retain students. This study investigated the precursors and outcomes of perceived value in achieving student loyalty in ODeL institutions. A quantitative approach was employed to gather data using self-administered online questionnaires, with 1430 responses. The partial least squares structural equation modeling technique was used to test the proposed model. The results indicate that an ODeL institution’s reputation and service quality positively influence student value, while the outcomes are trust, commitment, and student loyalty. However, institutional reputation was found to have more influence on student value than service quality, and commitment had more influence on loyalty than trust. While a number of studies have been conducted on the relationship between the variables/constructs, service quality and reputation as determinants of customer value and trust and commitment’s influence on loyalty, they do not show the differences in the magnitude of each variable. This study showed that although all these factors correlate and positively influence one another, there are major differences in the magnitude of influence. It is thus recommended that ODeL institutions should formulate strategies aimed at enhancing institutional reputation, value, and student commitment in order to retain student loyalty. Key words: Service quality, institutional reputation, open distance electronic learning, perceived value, commitment